Spontaneous liver rupture following SARS-CoV-2 infection in late pregnancy: A case report - Ambrož, Radek; Stašek, Martin; Molnár, Ján; Špička, Petr; Klos, Dušan; Hambálek, Jozef; Skanderová, Daniela (World journal of clinical cases, 2022)
BACKGROUND: Coronavirus disease-2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by systemic inflammatory response syndrome and vasculopathy. SARS-CoV-2 associated mortality ranges from 2% to 6%. Liver dysfunction was observed in 14%-53% of COVID-19 cases, especially in moderate severe cases. However, no cases of spontaneous hepatic rupture in pregnant women with SARS-CoV-2 have been reported. CASE SUMMARY: A 32-year-old pregnant patient (gestational age: 32 wk + 4 d) without any remarkable medical history or long-term medication presented with epigastralgia. Infectious, non-infectious, and pregnancy-related hepatopathies were excluded. Sudden onset of right subcostal pain with D-dimer and liver enzyme elevation was followed by shock with thrombocytopenia. While performing an emergency cesarean section, hemoperitoneum was observed, and the patient delivered a stillbirth. A 6-cm liver rupture at the edges of segments V and VI had occurred, which was sutured and drained. SARS-CoV-2 positivity on reverse transcription-polymerase chain reaction was confirmed. Further revisions for intrahepatic hematoma with hemorrhagic shock and abdominal compartment syndrome were performed. Subsequently, the patient developed hemoptysis, which was treated using bronchoscopic therapy and non-invasive ventilation. Liver tissue biopsy revealed hemorrhagic foci and necrosis with an irregular centrilobular distribution. Antiphospholipid syndrome and autoimmune hepatitis were also ruled out. Fetal death was caused by acute intrauterine asphyxia. CONCLUSION: This case reveals that pregnant women with SARS-CoV-2 infection may be predisposed to liver parenchyma disease with liver rupture.